2020
DOI: 10.1177/1073191120903382
|View full text |Cite
|
Sign up to set email alerts
|

Age Appropriateness of the Self-Report Strengths and Difficulties Questionnaire

Abstract: The self-report version of the Strengths and Difficulties Questionnaire is widely used in clinical and research settings. However, the measure’s suitability for younger adolescents has recently been called into question by readability analysis. To provide further insight into the age-appropriateness of the self-report Strengths and Difficulties Questionnaire, readability was assessed at the item level alongside consideration of item quality criteria, its factor structure was analyzed, and measurement invarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 64 publications
(166 reference statements)
0
29
0
Order By: Relevance
“…Finally, both the SDQ and SWEMWBS present some challenges in accuracy. It has recently been identified that the readability of the SDQ for younger adolescents is questionable and requires revision if it is to be self‐reported (Black, Mansfield, & Panayiotou, 2020). Similarly, SWEMWBS was found to be less understandable and relatable by an online population when compared with the YP‐CORE and SDQ (Sefi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both the SDQ and SWEMWBS present some challenges in accuracy. It has recently been identified that the readability of the SDQ for younger adolescents is questionable and requires revision if it is to be self‐reported (Black, Mansfield, & Panayiotou, 2020). Similarly, SWEMWBS was found to be less understandable and relatable by an online population when compared with the YP‐CORE and SDQ (Sefi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of indicators was restricted, given that the software used for the panel network analysis currently cannot handle more than around 30 (Epskamp, 2020b) and it is not appropriate to indiscriminately include highly similar indicators in networks (Fried & Cramer, 2017; Rhemtulla, Cramer, van Bork, & Williams, 2018). Items were therefore selected from those available in the dataset according to the following criteria: (a) conceptual domain, (b) item simplicity, given issues highlighted in this area (Black et al, 2020a), (c) descriptive and factor model statistics.…”
Section: Methodsmentioning
confidence: 99%
“…Younger ages (e.g., aged 13 only, 13-15) were examined for unique response patterns through item/scale diagnostics (Black et al, 2020). We also checked item and test invariance by demographics (e.g., age, first language) and clinical factors (self-reported psychiatric diagnosis, lifetime suicide attempts) through DIF and differential test functioning.…”
Section: Analysesmentioning
confidence: 99%